Copper(II) Complexes with Aromatic o‐Phosphorylated Phenols – Synthesis, Crystal Structures, and X‐ray Photoelectron Spectroscopy. Issue 27 (10th July 2013) - Shuvaev, Sergey; Bushmarinov, Ivan S.; Sinev, Ilya; Dmitrienko, Artem O.; Lyssenko, Konstantin A.; Baulin, Vladimir; Grünert, Wolfgang; Tsivadze, Aslan Yu.; Kuzmina, Natalia
Abstract: The structural properties of copper complexes with (2‐hydroxyphenyl)di‐ p ‐tolylphosphane oxide (CuL 1 2 ) and 3‐(2‐hydroxyphenyl)‐3, 4‐dihydro‐2 H ‐benzo[ f ][1, 5, 3]dioxaphosphepine 3‐oxide (CuL 2 2 ) are studied in detail. The o ‐phosphorylated phenols demonstrate both bridging and chelating behaviour, and the main reaction product is a coordination polymer containing dimeric Cu2 O8 fragments. The structural peculiarities of the o ‐phosphorylated phenols were revealed by single‐crystal X‐ray diffraction. The copper complexes are studied by single‐crystal and powder X‐ray diffraction, and IR, Raman and X‐ray photoelectron spectroscopy (XPS). The applicability of XPS spectroscopy to structural studies of coordination compounds with complex organic ligands is demonstrated with CuL 1 2 and CuL 2 2 . The results of ab initio structure solution and Rietveld refinement of the CuL 2 2 structure from powder data are augmented by PW‐PBE‐D calculations. Abstract : The formation of copper complexes with aromatic o ‐phosphorylated phenolates with both chelating and bridging configurations was demonstrated by single‐crystal and powder X‐ray diffraction. Photoelectron spectroscopy was utilized to reveal the coordination polyhedra around the copper ions in an amorphous copper complex.